A Self-Adaptive Trust Region Algorithm (Journal of Computational Mathematics, 2003)
In this paper we propose a self-adaptive trust region algorithm. The trust region radius is updated at a variable rate according to the ratio between the actual reduction and the predicted reduction of the objective function, rather than by simply enlarging or reducing the original trust region radius at a constant rate. We show that this new algorithm preserves the strong convergence property of traditional trust region methods. Numerical results are also presented.
Keywords: Trust region; Unconstrained optimization; Nonlinear optimization.